Methane Alleviates Lung Injury through the IL-10 Pathway by Increasing T Regulatory Cells in a Mouse Asthma Model. (30th June 2022) - Yao, Ying; Miao, Xiaoyong; Wang, Liping; Jiang, Zhengyu; Li, Lingxia; Jiang, Ping; Wang, Yifei; Jin, Aixia; Li, Na; Wang, Changli; Tan, Kezhe; Meng, Yan; et al.
Abstract : Allergic asthma is associated with allergen-induced airway hyperresponsiveness and inflammatory cell infiltration. While moderate-to-severe asthma with refractory symptoms is difficult to treat, methane is protective against organ damage. In this study, an asthmatic mouse model was established. Airway resistance under acetylcholine stimulation in asthmatic mice and histology of lung tissue injury were determined. EOS infiltration was determined by flow cytometry. Enzyme-linked immunosorbent assays (ELISAs) were performed for the determination of relevant cytokine levels in asthmatic mice with or without methane treatment. The potential mechanisms of methane under anti-IL-10 antibody intraperitoneal intervention were assessed by ELISA and flow cytometry. Pulmonary T regulatory cells (Tregs) were analyzed by flow cytometry, and anti-CD25 antibody was used to block them. Immunoblot analysis was performed to evaluate if methane played a role in the asthmatic lungs via the NF- κ B and MAPKs pathways. The results showed that methane significantly improved airway compliance, relieved asthma-induced lung injury, and reduced EOS accumulation and inflammatory mediators in the lungs of ovalbumin-treated asthmatic mice. Anti-IL-10 treatment diminished the ameliorating effect of methane on asthma. In addition, methane enhanced pulmonary Tregs in asthma, which could be blocked by the anti-CD25 antibody. Further analysis revealed that methane decreased p-p65/p65 and p-p38/p38 expression. In conclusion, methane is a readily available and inexpensive molecule potentially suitable for human use, which can alleviate asthma-induced lung injury and EOS infiltration through the IL-10 pathway by increasing Tregs and decreasing NF- κ B and p38 MAPK in a mouse model.